Cloning, sequence analysis, and functional study of the PeDof-4 gene in response to drought stress (Bangladesh Journal of Botany, 2024)
DNA-binding with one finger (Dof) was a functionally important gene in plant stress tolerance processes. The cloned full-length (849bp) passion fruit PeDof-4 gene was sequenced, which encodes  282 amino acids with the molecular formula C1274H1983N375O408S14, molecular weight 29529.87 u, and theoretical isoelectric point pI of 8.96. Evolutionary tree analysis showed that the PeDof-4-encoded proteins had a high degree of identity with Dof-encoded proteins in other plants. Blastp of the PeDof-4 encoded proteins revealed a closer affinity to the proteins encoded by the Dof of Theobroma cacao. The relative expression of the PeDof-4 gene was higher at 50% of the relative soil moisture content in the fluorescence qPCR experiments under different levels of drought stress.  Tissue-specific analysis showed that the highest expression of this gene was found in the roots. Overexpression of GUS gene under the PeDof-4 promoter inbidopsis thaliana showed that PeDof-4   could signiﬁcantly respond to drought stress.Bangladesh J. Bot. 52(3): 653-663, 2024 (September) Special